Mining for Candidate Genes in an Introgression Line by Using RNA Sequencing: The Anthocyanin Overaccumulation Phenotype in Brassica - Xie, Lulu; Li, Fei; Zhang, Shifan; Zhang, Hui; Qian, Wei; Li, Peirong; Zhang, Shujiang; Sun, Rifei (Frontiers in Plant Science, 2016)
Introgression breeding is a widely used method for the genetic improvement of crop plants; however, the mechanism underlying candidate gene flow patterns during hybridization is poorly understood. In this study, we used a powerful pipeline to investigate a Chinese cabbage (Brassica rapa L. ssp. pekinensis) introgression line with the anthocyanin overaccumulation phenotype. Our purpose was to analyze the gene flow patterns during hybridization and elucidate the genetic factors responsible for the accumulation of this important pigment compound. We performed RNA-seq analysis by using two pipelines, one with and one without a reference sequence, to obtain transcriptome data. We identified 930 significantly differentially expressed genes (DEGs) between the purple-leaf introgression line and B. rapa green cultivar, namely, 389 up-regulated and 541 down-regulated DEGs that mapped to the B. rapa reference genome. Since only one anthocyanin pathway regulatory gene was identified, i.e., Bra037887 (bHLH), we mined unmapped reads, revealing 2,031 de novo assembled unigenes, including c3563g1i2. Phylogenetic analysis suggested that c3563g1i2, which was transferred from the Brassica B genome of the donor parental line Brassica juncea, may represent an R2R3-MYB transcription factor that participates in the ternary transcriptional activation complex responsible for the anthocyanin overaccumulation phenotype of the B. rapa introgression line. We also identified genes involved in cold and light reaction pathways that were highly upregulated in the introgression line, as confirmed using quantitative real-time PCR analysis. The results of this study shed light on the mechanisms underlying the purple leaf trait in Brassica plants and may facilitate the use of introgressive hybridization for many traits of interest.